Oxidative stress produced by hyperthyroidism status induces the antioxidant enzyme transcription through the activation of the nrf-2 factor in lymphoid tissues of balb/c mice - Costilla, Melisa (2019)
Fil: Costilla, Melisa. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina